2014
DOI: 10.1016/j.msard.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term management of natalizumab discontinuation in a large monocentric cohort of multiple sclerosis patients

Abstract: Background: Several pPivotal and post-marketing studies showed demonstrated the efficacy and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 18 publications
1
52
0
1
Order By: Relevance
“…After a full-text review and removal of duplicates, 19 studies met the eligibility criteria for this review. One study was an RCT; 120 12 were prospective cohort studies; [121][122][123][124][125][126][127][128][129][130][131][132] and six were retrospective cohorts. [133][134][135][136] In 15 studies, participants were receiving natalizumab before discontinuing treatment due to safety issues, whereas in one study, 127 participants were receiving fingolimod.…”
Section: Review Questionmentioning
confidence: 99%
See 4 more Smart Citations
“…After a full-text review and removal of duplicates, 19 studies met the eligibility criteria for this review. One study was an RCT; 120 12 were prospective cohort studies; [121][122][123][124][125][126][127][128][129][130][131][132] and six were retrospective cohorts. [133][134][135][136] In 15 studies, participants were receiving natalizumab before discontinuing treatment due to safety issues, whereas in one study, 127 participants were receiving fingolimod.…”
Section: Review Questionmentioning
confidence: 99%
“…At 24 weeks after natalizumab cessation, there was a significant reduction in the annualized relapse rate between the pre-natalizumab period and the post-natalizumab period (2 vs 0.3; p = 0.009), 128 and a reduction in the mean number of relapses (1.1 vs 0.07), although no p values were reported, 120 according to fair quality evidence. At 52 weeks after natalizumab discontinuation, several studies of fair to poor quality reported a statistically significant reduction in the annualized relapse rate compared with that during the pre-natalizumab period 131,135,137,138 or described a reduction without statistical calculations. 123,126 However, other studies of fair quality reported no change in the annualized relapse rate and mean number of relapses between the two time periods.…”
Section: Review Questionmentioning
confidence: 99%
See 3 more Smart Citations